Pengaruh Profitabilitas, Likuiditas, Solvabilitas, Aktivitas, Dan Kebijakan Dividen Terhadap Harga Saham - Stella Levina, Elizabeth Sugiarto Dermawan (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
This research was conducted to determine the effect of profitability, liquidity, leverage, activity, and dividend policy toward stock prices. In this research profitability is measured by ROE, liquidity is measured by CR, leverage is measured by DER, activity is measured by TATO, and dividend policy is measured by DPR. Purposive sampling method is used to collect the sample. The number of samples used is 15 companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2015-2017 that meet the specified criteria. The analytical method used in this research is multiple linear regression. The program used to process the data is IBM SPSS 25. This research shows that profitability (ROE), liquidity (CR), leverage (DER) and activity (TATO) have a significant positive effect toward stock prices. On the other hand, dividend policy (DPR) has no significant effect toward stock prices despite showing that it is positively correlated.